2019
DOI: 10.1101/868190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PPARγ is a tumor suppressor in basal bladder tumors offering new potential therapeutic opportunities

Abstract: PPARactivation is a critical event in luminal muscle-invasive bladder cancer (MIBC) tumorigenesis, favoring both tumor cell growth and microenvironment modulation toward tumor immune escape. Conversely, the down-regulation of PPARactivity in basal MIBC suggests tumor suppressive effects in this subgroup. Here, we report genetic, epigenetic and functional evidence to support the tumor suppressor role for PPAR in basal bladder tumors. We identified hemizygous deletions, DNA hyper-methylation and loss-of-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…In basal bladder tumors, four non-recurrent loss-of-function PPARg mutations (S74C, F310S, E455Q, and H494Y, Figure 2) have been identified (130). All four PPARg mutants display significantly reduced transcriptional activities.…”
Section: Loss-of-function Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In basal bladder tumors, four non-recurrent loss-of-function PPARg mutations (S74C, F310S, E455Q, and H494Y, Figure 2) have been identified (130). All four PPARg mutants display significantly reduced transcriptional activities.…”
Section: Loss-of-function Mutationsmentioning
confidence: 99%
“…Biochemical and biophysical analysis of amino acid residues F310 and H494, situated in helix 3 and 12, respectively, indicated that both residues are essential for proper stabilization of helix 12. F310S and H494Y favor an inactive conformation, impairing both a proper release of corepressors and recruitment of coactivators (130). Basal tumors rely on EGFR signaling for growth (131).…”
Section: Loss-of-function Mutationsmentioning
confidence: 99%
“…A previous study showed that PPARγ F310S mutation was associated with basal bladder tumors. Further biochemical and structure-function analysis showed that the F310S mutation decreases PPARγ activity through the destabilization of helix 12, thereby impairing the release of corepressors and the recruitment of coactivators ( 16 ). Moreover, mechanisms of negative dominance and haploinsufficiency have both been suggested to explain the pathogenicity of PPARG mutations.…”
Section: Discussionmentioning
confidence: 99%